TO THE QUESTION OF ORGANIZATION OF DISTANCE LEARNING IN A FOREIGN LANGUAGE BASED ON INTERACTIVE FACILITIES - Pardaeva, Shakhodat (Журнал иностранных языков и лингвистики, 2021)
THIS ARTICLE IS ABOUT TO THE QUESTION OF ORGANIZATION OF DISTANCE LEARNING IN A FOREIGN LANGUAGE BASED ON INTERACTIVE FACILITIES